PENGARUH KUALITAS LAYANAN ADMINISTRASI AKADEMIK TERHADAP KEPUASAN MURID MAN PURWOREJO - Meilinda Putri; Isnaini Isnaini; Akhmad Shaiful Bakri (STKIP Pesisir Selatan, 2025)
This study aims to examine and reveal the extent to which the quality of academic administrative services affects student satisfaction at MAN Purworejo. Student satisfaction is considered one of the key indicators of the success of academic administrative services provided by the school. This research employs a quantitative approach using a survey method. The population of this study consists of all eleventh-grade students of MAN Purworejo, totaling 357 students. The sample was determined using the Slovin formula, resulting in a sample of 189 students. Data analysis was conducted using classical assumption tests, including the normality test and linearity test, to ensure that the data met the requirements for statistical analysis. Furthermore, hypothesis testing was carried out using the t-test (partial test). The results of the analysis show that the significance value of the t-test is 0.001, which is smaller than the significance level of 0.05. This indicates that the quality of academic administrative services has a significant effect on student satisfaction at MAN Purworejo. Therefore, the hypothesis stating that there is a significant influence of the quality of academic administrative services on student satisfaction is accepted, highlighting the importance of improving the quality of academic administrative services to enhance student satisfaction